Autoimmune Cholangitis: A Variant Syndrome of Autoimmune Hepatitis - Brij Sharma; Sujeet Raina; Rajesh Sharma (Case Reports in Hepatology)
Autoimmune cholangitis (AIC) or autoimmune cholangiopathy is a chronic inflammation of liver and a variant syndrome of autoimmune hepatitis (AIH). We present a case of an adult female who had biochemical features of cholestasis and transaminasemia but aminotransferases were not in the hepatitis range and had histological evidence of bile duct injury which was subsequently diagnosed as autoimmune cholangitis.